Land inventory analysis for urban agriculture – a case study of the City of Onkaparinga, South Australia - Sarker, Arif; Marinova, Dora; Bornman, Janet (2024)
Urban agriculture is one of the food system planning strategies that are increasingly recognised by planners and policymakers in Australia and around the world to address sustainability issues. However, determining available land for urban agriculture within the city space is extremely complex and problematic due to its high value and many competing demands. Identifying potential land in the form of a land inventory analysis using Geographic Information System (GIS) technologies is a widely used tool to facilitate urban agriculture. The study was conducted in 2022 with an objective to analyse the current practice of agricultural land inventory analysis and develop a methodological approach for identifying vacant land suitable for urban agriculture in a local government area. It uses as a case study the City of Onkaparinga, located on the southern fringe of Adelaide in South Australia. The latitude and longitude of City of Onkaparinga are -35.8680 and 138.57780 respectively. An inventory of vacant, unused, and underutilised public land available for urban agriculture within the local government area was developed as a guide for policymakers and planners to incorporate food into their urban planning strategy, using the City of Onkaparinga as a model system.